METODE TA’LILI SEBAGAI ALAT IJTIHAD HUKUM ISLAM (Pascasarjana Institut Agama Islam Almuslim Aceh, 2024)
The study of Islamic law in the history of its development is carried out using the bayani, ta'lili and istishlahi approaches. Bayani focuses legal studies on linguistic rules, istishlahi on the beneficial aspects and ta'lili on the optics of the logical reasons behind a law. This research focuses its study on the ta'lili method considering the rules of fiqhiyah agreed upon by the jurists